SIFAT PAPAN WOL KAYU DARI 10 JENIS KAYU NUSA TENGGARA BARAT - l M Sulastiningsih; Rodjak Memed; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The results of laboratory test of wood-wool board properties made fram ten wood species obtained from Nusa Tenggara province are reported in this paper. The properties tested were board density, moisture content, thickness reduction due Io compression and benJing strengih.The Study revealed that the average yield of wood-wool was 423,6 kg per cubic meter of log input. The wood-wool of Anthoceplus cadamba Miq. and Anthocephallus sp. must be soaked in cold water for 24 houn prior to manufacturing of wood-wool board, whereas she other species did not require soaking. The physical and mechanical properties of wood-wool board from nine wood species mineralized with CaCl2 solution were in conformity with the DIN 1101 standard. However, only three wood species mineralized with Ca (OH)2 suspension met the standard requirement.